Software Project Management Systems Using Kanban Method in the CV. Primavisi Globalindo - Ilmi, Muhammad Aliyya; Pradana, Fajar; Hayuhardhika Nugraha Putra, Widhy; Fajar (Universitas Nusantara PGRI Kediri, 2020)
Reducing the risk of failure in working on software projects is one of the successes for the company. It can be done by implementing project planning management properly. One important aspect of project management planning is scheduling. Scheduling includes recording human resources and tasks in the project. The Kanban method is one of the methods used to overcome problems in controlling project schedules. This study aims to develop a project scheduling system that applies the Kanban method. In this research, project management and scheduling system will be developed using the Kanban method. This system expected to be able to assist companies in handling projects. Kanban was chosen because it can easily respond to project changes, easily implemented, and company needs. In this study, unit testing was performed on the system's three main features and tested the validity of the system's 49 functional requirements. The usability test produces a value of 76. Based on the validation and usability test results, it can be concluded that the system is included in the acceptable category.